A MOOC for literature integrated language classroom: pedagogical suggestions for the development of Higher Order Thinking Skills (HOTS) - Mat Daud, Nuraihan; Mohamad Ali, Afiza; Mat Daud, Nor Shidrah; Juhary, Jowati; Mohd Mydin, Raihanah (rab Society of English Language Studies (ASELS), 2018)
An important component of language teaching is the development of higher order thinking skills (HOTS) among the students. In some language classes, this is done in the literature component of the curriculum. However, in many circumstances teachers are not trained on how to integrate critical thinking skills in literature integrated language learning classes. Training teachers nationwide can be costly to a country if the traditional way of in-service training is adopted. One of the ways to address this problem is by providing online training programmes. A viable alternative platform for online engagement is the Massive Open Online Course (MOOC) which has the potential to reach the mass. A training module would have to take into consideration the fact that different schools could be using different literary texts. Hence, the training module for teachers would need to focus on activities or pedagogical approaches rather than the text itself. This paper will focus on the aspects to consider when developing a MOOC for this purpose. This study will focus on Malaysian teachers who are expected to integrate HOTS into their literature lessons. When developing the materials, two important aspects that need to be considered are the components of HOTS and also the approaches that can be adopted. This paper discusses the approaches that can be applied to develop a specific aspect of HOTS. It focuses on the Malaysian teachers who are expected to integrate HOTS into their literature lessons.